Effectiveness of Organizational Network Analysis (ONA) on Global Competence and Work Productivity in Multinational Companies (Indonesia and Malaysia Country Study) - Pulungan, J. Suyuthi; Haryanto, Bambang; Puspita Dewi, Emi; Darmawan, Candra; Walian, Anang (International Journal Labs, 2024)
In a world full of uncertainty, companies need new methods to develop businesses that are closely related to work productivity. This productivity is influenced by leadership in the organization that is able to motivate employees to achieve company goals. Organizational Network Analysis (ONA) offers a unique approach in analyzing social relationships in organizations to improve productivity. Individual productivity depends on the competencies possessed, and global competence is an important thing that every individual must have to help companies compete and survive the challenges. The purpose of this study is to determine and analyze the effectiveness of organizational network analysis on global competence and work productivity in multinational companies. The method in this research is quantitative non-experimental. The number of samples in this study were 124 people. The data analysis technique uses the PLS or Partial Least Square method. The results showed that work productivity is inseparable from the role of ONA as a variable that can prove a strong relationship and the important role of ONA in organizational activities. And also the global competency variable is placed as a mediating variable with ONA that affects work productivity with the results of data processing from SMARTPLS 3.2.9 can still provide a significant and positive slice of influence. This research has implications for the development of organizational management strategies, especially in improving work productivity through the application of Organizational Network Analysis (ONA) and strengthening global competencies.